KETERAMPILAN BERPIKIR TINGKAT TINGGI DALAM PEWARNAAN SISI r-DINAMIS PADA GRAF KHUSUS - Maylisa, Ika Nur; Dafik, Dafik; Setiawani, Susi (Kadikma, 2015)
Abstract. Edge coloring -dynamic of a graph is a map , where , such that no two adjacent edges receive the same colors. An edge -dynamic -coloring is a proper -colouring of such that for each edge in , where is the neighborhood of and are the degree of while for a edge subset . The edge -dynamic chromatic number written as , is the minimum such that has an edge -dynamic -coloring. In this research develop edge coloring -dynamic on special graph, specially on graph, lobster graph, butterfly graph, diamond graph, friendship graph and star graph. The result from this research is a theorem that indicated minimum color for a graph G in topic “edge coloring -dynamic” and how the link between edge coloring with Higher Order Thinking Skill (HOTS). Keywords: edge coloring, -dynamic, chromatic number, HOTS